Pendidikan Kesehatan Tentang Dampak Rokok Terhadap Kualitas Hidup Pasien Asma Bronkial - Marlin Sutrisna; Ariyus Popsi Gito (Universitas Pahlawan Tuanku Tambusai, 2021)
Asthma recurrence can affect quality of life, but smoking can exacerbate the patient's condition so that it has an impact on quality of life. The purpose of this community service is to increase knowledge for puskesmas visitors about the impact of smoking on the quality of life of asthma patients. The method used is a question and answer discussion/discussion and the provision of booklets. The results obtained by the respondent's knowledge increased from before being given counseling to after being given counseling. The conclusion is that the counseling provided increases the respondents' knowledge about the impact of smoking on the quality of life of bronchial asthma patients. It is hoped that by doing this community service, asthma patients can stop smoking and stay away from cigarette smoke. Keywords: Quality of Life, Quality of Life, Counseling